2018
DOI: 10.1111/vru.12675
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic flexion/extension and non‐weight bearing ultrasonography is helpful for identifying manica flexoria tears in horses

Abstract: Lesions of the manica flexoria are a tenoscopic finding in horses with digital flexor tendon sheath tenosynovitis. This retrospective case series study describes the ultrasonographic findings in seven horses admitted for digital flexor tendon sheath swelling associated with lameness and tenoscopic confirmation of a manica flexoria tear. Six horses had a partial manica flexoria tear, one a complete rupture. The ultrasonographic examination included a static examination on the weight and non-weight bearing limb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(45 citation statements)
references
References 15 publications
0
32
0
2
Order By: Relevance
“…A promising technique to detect MF tears preoperatively, however, the study does only include cases that had a tenoscopically confirmed diagnosis and was not available for the majority of our cases (Garcia da Fonseca et al . ). It remains unknown in how many cases the presumptive diagnosis of a MF rupture was not confirmed by surgery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A promising technique to detect MF tears preoperatively, however, the study does only include cases that had a tenoscopically confirmed diagnosis and was not available for the majority of our cases (Garcia da Fonseca et al . ). It remains unknown in how many cases the presumptive diagnosis of a MF rupture was not confirmed by surgery.…”
Section: Discussionmentioning
confidence: 97%
“…), although Garcia da Fonseca et al . () recommend static ultrasonographic examination of the MF using a flexed limb position and dynamic ultrasonographic examination using flexion and extension positioning. A promising technique to detect MF tears preoperatively, however, the study does only include cases that had a tenoscopically confirmed diagnosis and was not available for the majority of our cases (Garcia da Fonseca et al .…”
Section: Discussionmentioning
confidence: 99%
“…Lesions of the manica flexoria are a tenoscopic finding in horses with digital flexor tendon sheath tenosynovitis. This retrospective case series study by Rita Martins Garcia da Fonseca and colleagues in Portugal, Belgium and Italy described the ultrasonographic findings in seven horses admitted for digital flexor tendon sheath swelling associated with lameness and tenoscopic confirmation of a manica flexoria tear .…”
Section: Ultrasonography To Identify Manica Flexoria Tearsmentioning
confidence: 99%
“…Allerdings wurden hier nur Untersuchungen an der stehenden, belasteten Gliedmaße durchgeführt. Die ultrasonographische Untersuchung der MF an der gebeugten und gestreckten unbelasteten Gliedmaße wurde in einer kleinen Fallserie (n = 7) bereits beschrieben (Garcia da Fonseca et al 2019). Zur präziseren Untersuchung der TBS wird empfohlen, den Ultraschallkopf nach lateral und medial zu verschieben, um Fehldiagnosen vorzubeugen, die z.…”
Section: Introductionunclassified
“…Die vorliegenden Untersuchungen ergaben, dass die Rupturen der MF zu 85 % medial und lediglich zu 15 % lateral vor-lagen. In der Literatur wird die Ruptur der MF mit 40 bis 52 % medial und mit 17 % bis 100 % lateral beschrieben(Wright und McMahon 1999, Arensburg et al 2011, Findley et al 2012, Diekstall et al 2019, Garcia da Fonseca et al 2019. In einer großangelegten Fallserie vonFindley et al (2012) traten 43 % (28/65) der MF-Rupturen medial und 17 % (11/65) lateral auf.…”
unclassified